The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13044-020-00084-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum TSH concentrations are associated with higher BMI Z-scores in southern Iranian children and adolescents

Abstract: Background Subclinical hypothyroidism is defined as elevated TSH levels while T4 or FT4 levels are normal. Elevated TSH levels are linked with obesity in adults. In a recent meta-analysis in Iran, 6.1% of children below 18 had obesity. Due to the low number of studies on the subject in children we, designed the study to assess the relation between BMI Z-score and TSH levels in children and adolescence. Method This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(60 reference statements)
1
7
0
3
Order By: Relevance
“…It is suggested that weight gain increases the incidence of thyroid autoimmunity. The association between obesity and the increased prevalence of autoimmune diseases, including AITDs, has been reported in several previous studies (23)(24)(25)(26)(27). The observations of this study were in line with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…It is suggested that weight gain increases the incidence of thyroid autoimmunity. The association between obesity and the increased prevalence of autoimmune diseases, including AITDs, has been reported in several previous studies (23)(24)(25)(26)(27). The observations of this study were in line with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Las posibles causas de los casos de hipotiroidismo subclínico con TSH elevada y T3 y T4 libres en concentraciones normales, incluyen disfunción neuroendocrina, resistencia a las hormonas tiroideas, modificación de la producción de TSH mediada por la leptina, y mutaciones del receptor de TSH (23). Nuestros resultados respecto al hipotiroidismo subclínico, concuerdan con estudios internacionales, donde se estima una prevalencia en niños obesos entre 7,5 y 23% (6,9,(24)(25)(26). La obesidad tiene influencia sobre la actividad del eje hipotálamo -hipófisis -tiroides, lo cual se evidencia mediante una elevación de la TSH en ausencia de déficit de Iodo y de alguna enfermedad tiroidea autoinmune (3,6).…”
Section: Discussionunclassified
“…De los obesos con hipotiroidismo, un alto porcentaje presentó T3 libre baja, o T4 libre baja, con TSH normales, es decir no hubo una respuesta compensadora de la glándula tiroides para normalizar los valores de las hormonas periféricas, por falta de estímulo hipotálamo o hipofisiario (13). Estos resultados difieren de estudios internacionales, quienes hallaron mayormente hipotiroidismo del tipo subclínico (6,9,(24)(25)(26). El hipotiroidismo primario constituye la enfer-medad endocrinológica más frecuente de la infancia, las formas hipotálamo-hipofisarias son poco frecuentes y generalmente se asocian a otras deficiencias hormonales, que son las que destacan y conducen al diagnóstico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In children, the level of TSH appears to be a stable and solid diagnostic parameter, however, its variability in laboratory tests has been observed [11]. On the other hand, there are some conditions in which the transitionally elevated TSH concentration is observed, with obesity being one of the welldocumented examples [12]. Studies concerning the influence of other transient conditions (e.g., inflammations) on TSH secretion are divergent [13,14].…”
Section: Introductionmentioning
confidence: 99%